2004
DOI: 10.1046/j.1365-3156.2003.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐injury malaria: a risk factor for wound infection and protracted recovery

Abstract: Summaryobjective To assess the impact of post-injury falciparum malaria on morbidity parameters in Cambodia.method Retrospective study of 227 trauma patients managed at a surgical centre in Battambang, Cambodia.results Within 10 days of the injury, 42.7% of the study population developed symptomatic malaria.In patients with post-injury malaria, the rate of wound infection was 36.1% compared with 10.0% in patients without symptomatic malaria (95% confidence interval for difference 15.2-36.9%). The average hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Traumatic events like tissue damage, blood loss, and surgery trigger cascades of inflammatory mediators to cause immunodepression with increased risk to develop malaria parasitaemia [ 26 ]. In a study among traumatized land mine and war victims in Cambodia [ 27 ], about 33% of asymptomatic malaria carriers developed posttrauma and postsurgery symptomatic malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic events like tissue damage, blood loss, and surgery trigger cascades of inflammatory mediators to cause immunodepression with increased risk to develop malaria parasitaemia [ 26 ]. In a study among traumatized land mine and war victims in Cambodia [ 27 ], about 33% of asymptomatic malaria carriers developed posttrauma and postsurgery symptomatic malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases affecting surgical outcome are endemic, and so is malnutrition. 13 In cal centers as part of external relief programs. Such emergency interventions often prove to be "too much, too late".…”
Section: Introductionmentioning
confidence: 99%
“…First, that preoperative malaria infection is an actionable independent predictor of readmission in the pediatric surgical population in rural Ghana. Previous studies have shown that malaria is a leading cause of perioperative hyperpyrexia, increases the rate of surgical site infections, increases postoperative recovery and that surgery can cause reactivation malaria [23][24][25][26][27][28]. The burden of malaria infection in this region is highest in the pediatric population due to the immunological and behavioral drivers [29].…”
Section: Discussionmentioning
confidence: 99%